A New Supplement to Spiritual Leadership from Spiritual Intelligence Conceptions and Etymologic Research - Michael Hagemann (International Journal of Management, Knowledge and Learning, 2022)
Purpose: This study identifies, compiles and compares different definitions of Spiritual Intelligence to detect common principles, it reviews the historical emergence of the word “spiritual” and proposes a new construct of Spiritual Intelligence.